2018
DOI: 10.1101/293647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of the UK honey bee (Apis mellifera) metagenome

Abstract: The European honey bee (Apis mellifera) plays a major role in pollination and food production, but is under threat from emerging pathogens and agro-environmental insults. As with other organisms, honey bee health is a complex product of environment, host genetics and associated microbes (commensal, opportunistic and pathogenic). Improved understanding of bee genetics and their molecular ecology can help manage modern challenges to bee health and production. Sampling bee and cobiont genomes, we characterised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Recently, a novel trypanosomatid parasite was discovered and named L. passim 7 . L. passim seems to be more prevalent than C. mellificae [7][8][9][10][11][12][13][14][15][16][17][18] . Although the association of L. passim infection with winter mortality of honey bee colonies was suggested in several studies 19,20 , the effects of L. passim infection on honey bee health and colony survival remain poorly understood.…”
mentioning
confidence: 95%
“…Recently, a novel trypanosomatid parasite was discovered and named L. passim 7 . L. passim seems to be more prevalent than C. mellificae [7][8][9][10][11][12][13][14][15][16][17][18] . Although the association of L. passim infection with winter mortality of honey bee colonies was suggested in several studies 19,20 , the effects of L. passim infection on honey bee health and colony survival remain poorly understood.…”
mentioning
confidence: 95%
“…Later, in 2015, another novel trypanosomatid parasite infecting honey bees was discovered and named L. passim (Schwarz et al, 2015). L. passim was found to be more prevalent than C. mellificae (Schmid-Hempel and Tognazzo, 2010; Morimoto et al, 2013; Cepero et al, 2014; Ravoet et al, 2014, 2015; Cersini et al, 2015; Schwarz et al, 2015; Arismendi et al, 2016; Cavigli et al, 2016; Stevanovic et al, 2016; Vavilova et al, 2017; Regan et al, 2018) and fewer honey bee colonies were reported to be infected by C. mellificae (Ravoet et al, 2015). Thus, L. passim rather than C. mellificae is likely to be associated with the previously reported winter mortality of honey bee colonies (Ravoet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although these protocols are designed around bees and their shared pathosphere [28][29][30][31] , they can easily be adapted to other groups of organism with common pathogens and distributions. The protocols are based on the detection and quanti cation of pathogen nucleic acid in a sample, rather than the disease consequences of the presence and loads of these pathogens for individual bee species 18 .…”
Section: Applications Of the Methodsmentioning
confidence: 99%